The effects of 15 minutes power nap on muscular power performance among Pencak Silat university athletes / Ain Syafiqah Bidin - Bidin, Ain Syafiqah (Faculty of Sport Sciences and Recreation, 2020)
The purpose of this study was to measure the effect of 15 minutes power nap on muscular power performance among Pencak Silat university athletes. Thirty one athletes (N=31) from University Technology MARA (UiTM), University Malaya (UM), and University Pendidikan Sultan Idris (UPSI) were selected purposely to participate for current study. A pre-post pre experimental design was utilized in this study to measure the power nap effect in muscular power performance. All samples were required to get 15 minutes of power nap before they were tested on adopted Standing Broad Jump to measure the muscular power. This study result has showed 15 minutes of power naps has significant contributed to a positive changes in muscular power performance which is the t value is t (30) =-2.74, p <0.05 (p<0.01). Thus, this study suggested that a short naps, 15 minutes can enhance muscular power performance in amateur Pencak Silat university athletes. Considering these finding for future studies, the researcher can increase the sample size to gain more validity, reliability, and normality in the study and also should use an electronic device to provide athletes’ sleeping patterns in potentially reasoning for the quality of naps. Future researchers also may monitor sleeping patters night before the test as it has an effect on subsequent sleep quality and quantity and focus on various durations of naps to determining the optimal duration for the performance.